2021
DOI: 10.1126/scitranslmed.abi8631
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 mRNA vaccines drive differential antibody Fc-functional profiles in pregnant, lactating, and nonpregnant women

Abstract: Pregnant and lactating women develop distinct antibody Fc profiles in response to the mRNA-1273 and BNT162b2 vaccines compared to nonpregnant women.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
80
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 60 publications
5
80
0
Order By: Relevance
“…We found that the timing of immunization during pregnancy is important to ensure transplacental transfer of protective antibodies to the neonate, and during critical windows of immune vulnerability during early infancy. Consistent with prior studies showing robust immune responses to mRNA vaccination 14,15,17 , we found high levels of IgG after two doses of mRNA vaccine. However, completion of the vaccination series well before delivery was important to ensure transfer of antibodies to the infant.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We found that the timing of immunization during pregnancy is important to ensure transplacental transfer of protective antibodies to the neonate, and during critical windows of immune vulnerability during early infancy. Consistent with prior studies showing robust immune responses to mRNA vaccination 14,15,17 , we found high levels of IgG after two doses of mRNA vaccine. However, completion of the vaccination series well before delivery was important to ensure transfer of antibodies to the infant.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to prior studies 14,15,17 , we found that mRNA vaccination during pregnancy led to an increase in anti-SARS-Cov-2 IgG following dose 1 (n=7, mean 388.6, SD 224.8 RFU) and an even further robust increase after vaccination dose 2 (n=12, mean 3214, SD 1383 RFU). Anti-SARS-CoV-2 IgM (n=7, mean 53.3, SD 50.2 RFU) was detected in two maternal participants following dose 1, but only 1 participant following dose 2 (n=12, mean 23.8, SD 17 RFU, Fig 1).…”
Section: Mrna Vaccination In Pregnancy Leads To a Robust Antibody Responsesupporting
confidence: 89%
See 1 more Smart Citation
“…Further, our results showing a sustained anti-RBD antibody response in milk may have implications for the durability of vaccine-induced milk antibodies. Indeed, similar to SARS-CoV-2 infection and maternal vaccination against other respiratory pathogens ( 20 , 21 ), recent data demonstrate that in the days and weeks following maternal COVID-19 vaccination, a robust IgG-dominant milk antibody response is induced ( 22 25 ), although the longer-term durability of the milk-borne antibody response remains to be elucidated. Similarly, the mechanisms underlying the persistence or lack of specific antibodies in human milk are not well understood, but may be related to differences in the course of the infection, recurrent exposures and/or the migration of long-lived plasma cells from mucosal sites to the mammary gland ( 26 28 )…”
Section: Discussionmentioning
confidence: 99%
“…During gestation there is facilitated transfer of maternally derived antibodies through the binding of the neonatal Fc receptor in the synctiotrophoblast layer 29 . Differences in glycosylation 30,31 , FcR/FcRn binding affinity 17,32 , preferential IgG subclass transfer 33,34 may be different in functional neutralizing antibodies as compared to total IgG antibody transfer.…”
Section: Discussionmentioning
confidence: 99%